4D printed hydrogels: fabrication, materials, and applications - Dong, Yuting (2020)
4D printed objects are 3D printed structures whose shape, property, and functionality are able to self‐transform when exposed to a predetermined stimulus. The emerging field of 4D printing has attracted wide interest from both academia and industry since first introduced in 2013. Stimuli‐responsive hydrogels have become a competitive and versatile group of materials for 4D printed devices due to their good deformability, promising biocompatibility, simple manufacturing, and low cost. This review aims to provide a summary of the current progress of hydrogel‐based 4D printed objects and devices based on their fabrication techniques, materials, and applications. Herein, presented are: the characteristics of different additive manufacturing methods such as direct ink writing, fused deposition modeling, and stereolithography; the properties of various stimuli‐responsive hydrogels such as poly(N ‐isopropylacrylamide) and poly(N ,N ‐dimethylacrylamide), alginate, etc.; and diverse applications of 4D printed hydrogels such as actuators, cellular scaffolds, and drug release devices. Opportunities and challenges for 4D printed hydrogels are discussed and prospects for future development are elaborated.